Development of a synbiotic longan beverage: a nutritious and functional blend - Sakuntasri, K.; Kwanmuang, P.; Massa, S.; Krusong, W.; Charoenrat, T.; Pan-Utai, W.; Pornpukdeewattana, S. (My University, 2025)
Synbiotic foods, which synergistically combine probiotics and prebiotics, have garnered attention for their potential health benefits. In line with this trend, this study aimed to develop a synbiotic beverage using longan fruit as the base and fructo-oligosaccharides (FOS) as the prebiotic source. Two strains of Lactobacillus probiotics, Lactobacillus casei 431 and Lactobacillus plantarum KM001, were used to ferment the longan juice with and without FOS. Total soluble solids, reducing sugar, pH, total acid production, and viable cell count of Lactobacillus microorganisms were evaluated to determine the optimal fermentation duration. The findings indicated that fermenting the juice for 12 hrs at 37°C aligned with the criteria established by the FAO/WHO for probiotic foods. Furthermore, compared to L. casei 431, the longan juice containing FOS fermented with L. plantarum KM001 showed a better survival rate in a simulated gastrointestinal environment. Additionally, the microorganism count in this beverage remained relatively constant throughout its 28-days shelf life at 4°C. These findings underscore the synbiotic longan beverage as a functional drink that combines viable probiotics with prebiotic FOS.
Keywords: Fructo-oligosaccharides; Lactobacillus probiotic; Longan fruit; Prebiotic; Probiotic; Synbiotic beverage